EFFECT OF PROBLEM BASED LEARNING (PBL) MODEL AND LEARNING MOTIVATION ON LEARNING OUTCOMES OF CLASS XI SEMESTER II SUBJECT MATTER OF FLUID DYNAMICS IN SMA - Yosico Indagiarmi; Abdul Hakim Siregar (Jurnal Pendidikan Fisika, 2016)
This research aims to determine the effect of Problem Based Learning model on the student’s learning outcomes in the subject matter dynamic fluid. This research is a quasi-experimental study with two group design Pre-test and post-test, this study population was all students of class XI SMA Private Panca Budi Medan TP 2014 / 2015. The samples were taken by cluster random sampling technique, which consists of two classes, PBL applied in experiment class and conventional learning applied in control class, Data was obtained by using 12 essay instruments, observation ofactivities, attitudes and skills of students. From the analysis of the data for the experiment class gained an average of 30.5 Pre-test and the average value of Post-test 74.2. Control classes gained an average of 33.2 Pre-test and average Post-test 65.8. Both classes are normally distributed and have a homogen variation. t count was 2,016 at the real level of 0.05 where t count was 2,407 and t count > t table. So that there is significant effect of Problem Based Learning (PBL) to student’s learning result in the subject matter dynamic fluid of class XI SMA Private Panca Budi Medan TP 2014/2015.